Violence and Power in Hannah Arendt - Prayer Elmo Raj (Journal of Contemporary Poetics, 2020)
Hannah Arendt rejects the correlation of politics and violence by disputing that violence is not essentially intrinsic to the political. Violence and power are not identical. Power is instinctively configured by combined and mutual functioning of the multiplicity and differences of citizens. Violence is aphasic, that which aims to detach the citizens by interrupting the civic borders binding them in their deeds. Power is self-binding because it consolidates political agents and public space. However, violence is solely instrumental because it aims to accomplish a defunctive end through force. Power engenders the institution of a “transitory consensus” instigating the opportunity of contention and conflict but violence is catastrophic, incompetent of being creative. Arendt examines how politics has been mutated into violence. In order to consider politics as violence, one has to challenge the complementary correspondence of politics and violence. Countries that press on preventive wars press themselves as good fighting against the evil so as to redeem the future and humanity. To arrive at these goals, countries break international agreements asserting economic and political dominance in an uneven world. While terrorists use violence to destroy their enemies, the use of nuclear and biological weapons by the states could extinguish the entire humanity. States enforce stringent policies against immigrants, refugees and justice movements that coordinate the unemployed, displaced, homeless and the rejected sections of the society. This paper is an attempt to critically examine Arendt’s speculations on the interconnection between power and violence and the implications of Arendt’s theory in the context of global violence.